2014
DOI: 10.4028/www.scientific.net/amr.945-949.424
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic Annotation Framework to Assist the Knowledge Interoperability along a Product Life Cycle

Abstract: The interoperability among a variety of systems, in or across manufacturing enterprises, has been widely accepted as one of the important factors that affects the efficiency of production. The aim of this study is to deal with the semantic interoperability issues in a product lifecycle management environment. Through the investigation of related works, the need for the formalization of semantic annotation was discovered. This paper addresses this drawback and introduces a framework that uses formalized semanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Based on these three hypotheses, the objective of the paper is to provide an extension of previous publications of the authors (Liao et al 2014a(Liao et al , 2014b, through a more complete description of the semantic annotation method and a more detailed presentation of the case study. Among all the improvements in each section, several major ones are listed as examples.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these three hypotheses, the objective of the paper is to provide an extension of previous publications of the authors (Liao et al 2014a(Liao et al , 2014b, through a more complete description of the semantic annotation method and a more detailed presentation of the case study. Among all the improvements in each section, several major ones are listed as examples.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Morris et al, 2004) a lesson learned from CASE tool integration is that a primary barrier to increased interoperability is the difficulty of reaching such agreements (Flahive & Jakobsson, 2008). This can be, in part, due to stakeholders having different backgrounds, heterogeneous expertise, unique knowledge, particular needs and specific practices (Bonacin et al, 2014;Liao et al, 2014).…”
Section: Challengesmentioning
confidence: 99%
“…One of the widely recognized methods to deal with semantic gaps is to semantically enrich the exchanged information through an ontology. Several studies highlighted and proved the advantages of applying semantic annotations on various kinds of models, which represent a product from different perspectives (Liao et al, 2014). For example, the ontology proposed by Qin et al (Qin et al, 2017) was found to enable the automatic check of consistency, reason out the new knowledge and implement the semantic interoperability of Composite Positional Tolerance (CPT) information.…”
Section: Information Enriched With Ontologiesmentioning
confidence: 99%
See 1 more Smart Citation